GE_GERICHTE C/22218/2012 vom 20. Juni 2014 - GE Cour de justice (2014)
OBLIGATION D'ENTRETIEN; ENFANT; DIVORCE; LIQUIDATION DU RÉGIME MATRIMONIAL; MESURE PROVISIONNELLE | CC.114; CC.133; CC.208; CC.285